Climatic oscillations in the production of Eucalyptus benthamii x E. dunnii shoots in mini-clonal hedge - Pereira Pires, Patrícia; Wendling, Ivar; de Souza, Anderson Marcos; Guedes Coelho, Alexandre Siqueira (BOSQUE, 2017)
Detailed knowledge on the factors influencing the production of minicuttings, especially focusing on management and environmental optimization is important. Therefore, this study aimed at evaluating the influence of temperature, relative humidity and PAR (photosynthetically active radiation) and their oscillations in mini-clonal hedges of three E. benthamii x E. dunnii hybrid clones regarding survival, vigor and productive capacity of ministumps. A mini-clonal hedge with a semi-hydroponic system was formed, with five replicates of five ministumps per clone, submitted to 41 successive collections of minicuttings during one year. A multiple linear regression model for minicutting production was adjusted according to maximum, average and minimum climatic variables, considering a period from 0 until 16 weeks before collection. Ministumps from three clones showed 100 % survival throughout the year. Clone 1 showed higher production (8,000 minicuttings m-2 month-1) and clone 3 showed the lowest values for this variable (less than 5,000 minicuttings m-2 month-1). The adjusted multiple linear regression model was formed by the maximum PAR, máximum humidity and temperature range of different weeks before collection. Maximum PAR (1,440-1,600 μmol m-² s-1) was the most influential variable in the adjusted model and positively related to minicutting productivity. Based on ideal climatic values found by the regression model, it is possible to suggest that climatic oscillations do not favor ministump development.